2018
DOI: 10.1016/j.jcp.2017.12.017
|View full text |Cite
|
Sign up to set email alerts
|

A modal approach based on perfectly matched layers for the forced response of elastic open waveguides

Abstract: This paper investigates the computation of the forced response of elastic open waveguides with a numerical modal approach based on perfectly matched layers (PML). With a PML of infinite thickness, the solution can theoretically be expanded as a discrete sum of trapped modes, a discrete sum of leaky modes and a continuous sum of radiation modes related to the PML branch cuts. Yet with numerical methods (e.g. finite elements), the waveguide cross-section is discretized and the PML must be truncated to a finite t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…In the latter case, the ingoing modal coefficients are obtained from the modal decomposition of the forced response (see Ref. [33]), further propagated analytically and enforced to the appropriate cross-section boundary. The subscript + denotes outgoing (scattered) modes.…”
Section: Hybrid Fe-modal Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter case, the ingoing modal coefficients are obtained from the modal decomposition of the forced response (see Ref. [33]), further propagated analytically and enforced to the appropriate cross-section boundary. The subscript + denotes outgoing (scattered) modes.…”
Section: Hybrid Fe-modal Approachmentioning
confidence: 99%
“…These modes are often called PML modes (or Berenger modes). Although PML modes are non-intrinsic to the physics (they resonate mainly in the PML region), their modal superposition enables to accurately reconstruct the forced response of an elastic open waveguide [33]. Nevertheless, their contribution remains unclear as far as scattering problems are considered.…”
Section: Introductionmentioning
confidence: 99%
“…is the general orthogonality relation in open waveguides[111], which is similar with Auld's real orthogonality relation[102].…”
mentioning
confidence: 75%
“…In addition, it has been demonstrated that the PML 5. Nonlinear Ultrasonic Guided Waves in Open Waveguides modes mainly oscillate in the PML region and only contribute to long-term diffraction, geometrical decay of the field [111] which is of little interest in the context of NDT, so that the sums can only run over all trapped and leaky modes.…”
Section: Nonlinear Ultrasonic Guided Waves In Open Waveguidesmentioning
confidence: 99%
See 1 more Smart Citation